Inflorescence and floral traits of the Colombian species of Tristerix (Loranthaceae) related to hummingbird pollination (2017)
ABSTRACT: Floral diversification in Loranthaceae reaches its highest peak in the Andes. The flowers of the exclusively Andean genus Tristerix exhibit tubular and vividly coloured flowers pollinated by hummingbirds. We studied inflorescence and flower morphoanatomy of the two Colombian species, T.longebracteatus and the highly endangered T.secundus. Both species have terminal racemes with up to 26 ebracteolate flowers, of which the proximal one opens and sets fruits first. The slightly irregular calyx initiation is followed by the simultaneous initiation of petals and the successive initiation of stamens. Anthesis is fenestrate, explosive, and triggered by the tension of the style against the abaxial petals, a mode so far not reported in Loranthaceae. Anthetic petals spread symmetrically in T.longebracteatus and asymmetrically in T.secundus. Nectar is produced by a supraovarial disk and by the petal mesophyll. Floral lifespan lastsup to 20 days. The hummingbirds Eriocnemisvestita and Pterophanes cyanopterus are the likely pollinators of T.secundus. Morphologicaltraits are inconclusive to support one of the two competing sister group relationships that involve Tristerix, as the lack of cataphylls in renewal shoots links Ligaria and Tristerix, whereas the terminal inflorescences support its relationship with Desmaria and Tupeia.